2019
DOI: 10.1055/a-0902-4467
|View full text |Cite
|
Sign up to set email alerts
|

Self-study of the non-extension sign in an e-learning program improves diagnostic accuracy of invasion depth of early gastric cancer

Abstract: Background and study aims We developed an e-learning program for endoscopic diagnosis of invasion depth of early gastric cancer (EGC) using a simple diagnostic criterion called non-extension sign, and the contribution of self-study quizzes to improvement of diagnostic accuracy was evaluated. Methods We conducted a prospective randomized controlled study that recruited endoscopists throughout Japan. After completing a pretest, the participants watched video lectures and undertook post-test 1. The part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…However, longer term follow-up is difficult, particularly in super-elderly patients because their prognoses are understandably not very long. Third, the cancer invasion depth in the conservative treatment group was diagnosed endoscopically only, although accuracy for diagnosis of invasion depth of EGC by conventional endoscopy was relatively high, reported to be around 75–80% in Japan [34]. In this study, 39 cases (84.8%) of the ESD group were diagnosed as cT1a at the time of initial diagnosis, and the positive predictive value was 76.9%, similar to previously reported.…”
Section: Discussionsupporting
confidence: 84%
“…However, longer term follow-up is difficult, particularly in super-elderly patients because their prognoses are understandably not very long. Third, the cancer invasion depth in the conservative treatment group was diagnosed endoscopically only, although accuracy for diagnosis of invasion depth of EGC by conventional endoscopy was relatively high, reported to be around 75–80% in Japan [34]. In this study, 39 cases (84.8%) of the ESD group were diagnosed as cT1a at the time of initial diagnosis, and the positive predictive value was 76.9%, similar to previously reported.…”
Section: Discussionsupporting
confidence: 84%
“…9). 7 Assessed for eligibility (n=439) The third study showed that the "accumulation of experi ence", achieved by repeated practice using the 100-case self-study training, consolidated the learning "technique" and "knowledge" and increased the diagnostic ability of endoscopists of EGC.…”
Section: E-learning Groupmentioning
confidence: 99%
“…5 To address these difficulties, we developed three types of web-based e-learning systems, tested each through randomized controlled trials (RCTs), and demonstrated their usefulness in ensuring correct and precise endoscopic diagnosis of EGC. [5][6][7] In this review, we introduce the basic diagnostic systems employed in e-learning, the outcomes of RCTs testing the usefulness of these three e-learning systems, and our future projects.…”
mentioning
confidence: 99%
“…Indeed, preoperative CT could not detect LNM in 90% of patients with LNM who underwent additional gastrectomy after non-curative ER [ 84 ]. Non-extension sign is considered a reliable finding for pT1b-SM2 by non-magnifying endoscopy, but its diagnostic accuracy in a prospective e-learning study was 80% at most [ 107 ]. The efficacy of EUS for diagnosing invasion depth of EGC is controversial [ 108 , 109 ]; however, these are retrospective studies, and a prospective study is required to accurately identify its diagnostic utility.…”
Section: Current Issues and Future Perspectivementioning
confidence: 99%